Long-term outcome and safety of prolonged bedaquiline treatment for multidrug-resistant tuberculosis - Guglielmetti, Lorenzo; Jaspard, Marie; Le Dû, Damien; Lachâtre, Marie; Marigot-Outtandy, Dhiba; Bernard, Christine; Veziris, Nicolas; Robert, Jérôme; Yazdanpanah, Yazdan; Caumes, Eric; Fréchet-Jachym, Mathilde (The European respiratory journal, 2017)
Bedaquiline, a recently approved drug for the treatment of multidrug-resistant tuberculosis (MDR-TB), is recommended for a duration of 24 weeks. There are scarce data on patients treated with this drug outside clinical trials.All MDR-TB patients who started treatment from January 1, 2011 to December 31, 2013 and received ≥30 days of bedaquiline were included in a multicentre observational cohort.Among 45 MDR-TB patients, 53% harboured isolates resistant to both fluoroquinolones and second-line injectables, and 38% harboured isolates resistant to one of these drug classes. Median bedaquiline treatment duration was 361 days and 33 patients (73%) received prolonged (>190 days) bedaquiline treatment. Overall, 36 patients (80%) had favourable outcome, five were lost to follow-up, three died, and one failed and acquired bedaquiline resistance. No cases of recurrence were reported. Severe and serious adverse events were recorded in 60% and 18% of patients, respectively. Values of Fridericia-corrected QT interval (QTcF) >500 ms were recorded in 11% of patients, but neither arrhythmias nor symptomatic cardiac side-effects occurred. Bedaquiline was discontinued in three patients following QTcF prolongation. No significant differences in outcomes or adverse events rates were observed between patients receiving standard and prolonged bedaquiline treatment.Bedaquiline-containing regimens achieved favourable outcomes in a large proportion of patients. Prolonged bedaquiline treatment was overall well tolerated in this cohort.